OPTIMIZATION OF RECURRENT THERAPY BRONCHOBSTRUCTIVE SYNDROME IN CHILDREN (World Bulletin of Public Health, 2023)
The results of anamnestic, conventional clinical laboratory and special examination methods in 40 children with recurrent broncho-obstructive syndrome were studied. The efficacy of Montelukast sodium in bronchial obstruction was determined depending on the severity of clinical and instrumental data
Keywords: recurrent course; broncho-obstructive syndrome in children